INTERROGATING EPISTEMIC FOUNDATIONS - Victor J. Pitsoe (Annals of the University of Craiova for Journalism, Communication and Management)
Offering convenient and adaptable learning opportunities on a global scale, open distance e-learning (ODeL) has become a game-changer in the field of higher education. But we must look closely at its epistemic underpinnings. Through a critical lens, this article investigates ODeL's epistemic desiderata and how they might promote the creation and sharing of knowledge in a way that is equitable, inclusive, and socially just. By highlighting the voices of the underrepresented and questioning established power structures, ODeL seeks to democratise education. However, its revolutionary potential is impeded by obstacles like digital inequality and commercialization. Innovative solutions that put pedagogy ahead of profit and equity ahead of exclusion are necessary to address these challenges. These difficulties can be lessened through efforts such as culturally responsive curriculum design, open educational resources, and inclusive technological infrastructures. By incorporating these strategies, ODeL can reach its full potential as a tool for democratising knowledge and empowering learners in various settings, thus achieving epistemic liberation.